Analyzing the financial position of a marketing consultancy firm: a comprehensive financial analysis of Unitrend Limited - Fiaz, Abul kashem Ahmed (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.